2003
DOI: 10.1080/02724980244000558
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Efficacy of Different forms of Knowledge of Results for the Learning of a New Relative Timing Pattern

Abstract: The goal of the present study was to determine the relative efficacy of verbal and auditory knowledge of results for promoting learning of a new constrained relative timing pattern. In a series of four experiments we compared the efficiency of verbal knowledge of results to that of auditory knowledge of results. The results of all four experiments revealed that verbal knowledge of result is a very effective source of information to promote learning of a new imposed relative timing pattern. Auditory knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…While the assumption of strong parallel fiber inputs on Purkinje cells and inhibition as a sculpting lateral mechanism continues to dominate modern cerebellar theories (Mauk and Ohyama, 2004; Hong and Optican, 2008), there is actually little experimental evidence that natural patterns of afferent cortical activation actually produce beam-like patterns of either excited or inhibited Purkinje cells (Bell and Grimm, 1969; Eccles et al, 1972; Bower and Woolston, 1983; Kolb et al, 1997; Cohen and Yarom, 1998; De Jaeger and Proteau, 2003; Holtzman et al, 2006; Heck et al, 2007; Rokni et al, 2007; de Solages et al, 2008). Instead Purkinje cells either activated or inhibited by peripheral stimuli are found in patches, not beams (Eccles et al, 1972; Bower and Woolston, 1983; Gao et al, 2006) whose locations, when measured, are found to be in close proximity to activated regions of the granule cell layer (Bower and Woolston, 1983; Kolb et al, 1997; Cohen and Yarom, 1998; De Jaeger and Proteau, 2003; Lu et al, 2005; Rokni et al, 2007; Brown and Ariel, 2009).…”
Section: Are There Naturally Occurring Parallel Fiber Induced Purkinjmentioning
confidence: 99%
See 1 more Smart Citation
“…While the assumption of strong parallel fiber inputs on Purkinje cells and inhibition as a sculpting lateral mechanism continues to dominate modern cerebellar theories (Mauk and Ohyama, 2004; Hong and Optican, 2008), there is actually little experimental evidence that natural patterns of afferent cortical activation actually produce beam-like patterns of either excited or inhibited Purkinje cells (Bell and Grimm, 1969; Eccles et al, 1972; Bower and Woolston, 1983; Kolb et al, 1997; Cohen and Yarom, 1998; De Jaeger and Proteau, 2003; Holtzman et al, 2006; Heck et al, 2007; Rokni et al, 2007; de Solages et al, 2008). Instead Purkinje cells either activated or inhibited by peripheral stimuli are found in patches, not beams (Eccles et al, 1972; Bower and Woolston, 1983; Gao et al, 2006) whose locations, when measured, are found to be in close proximity to activated regions of the granule cell layer (Bower and Woolston, 1983; Kolb et al, 1997; Cohen and Yarom, 1998; De Jaeger and Proteau, 2003; Lu et al, 2005; Rokni et al, 2007; Brown and Ariel, 2009).…”
Section: Are There Naturally Occurring Parallel Fiber Induced Purkinjmentioning
confidence: 99%
“…Instead Purkinje cells either activated or inhibited by peripheral stimuli are found in patches, not beams (Eccles et al, 1972; Bower and Woolston, 1983; Gao et al, 2006) whose locations, when measured, are found to be in close proximity to activated regions of the granule cell layer (Bower and Woolston, 1983; Kolb et al, 1997; Cohen and Yarom, 1998; De Jaeger and Proteau, 2003; Lu et al, 2005; Rokni et al, 2007; Brown and Ariel, 2009). Those few in vivo reports claiming to demonstrate the presence of beams either mapped Purkinje cell responses without reference to activity in the granule cell layer (Garwicz and Andersson, 1992; Jorntell and Ekerot, 2002; Heck et al, 2007), employed electrical rather than natural forms of afferent stimulation (Jorntell and Ekerot, 2002), or drew their conclusions based on patterns of activity obtained in completely different animals (Jorntell and Ekerot, 2002, 2006).…”
Section: Are There Naturally Occurring Parallel Fiber Induced Purkinjmentioning
confidence: 99%
“…While Purkinje cells do respond along parallel-fiber-activated beams in response to direct electrical stimulation of the molecular layer (Eccles et al 1966;Gao et al 2006;Wang et al 2011), when the cerebellum is activated from the sensory periphery, responding Purkinje cells are not found in beams, but instead are clustered in isolated patches (Bower and Woolston 1983;Dizon and Khodakhah 2011;Eccles et al 1972b;Gao et al 2006). When the locations of those responding Purkinje cell layer patches are determined carefully, they are consistently found to overlie activated regions of the granule cell layer (Bower and Woolston 1983;Brown and Ariel 2009;Cohen and Yarom 1998;De Jaeger and Proteau 2003;Dizon and Khodakhah 2011;Kolb et al 1997;Lu et al 2005;Rokni et al 2007). This relationship is shown diagrammatically in Fig.…”
Section: What Do Parallel Fibers Do To Purkinje Cells?mentioning
confidence: 83%
“…While it seems reasonable to assume that an excitatory input as massive as that of the parallel fibers would directly drive somatic spiking, the experimental fact is that there is little experimental evidence that they do (Bell and Grimm 1969;Bower and Woolston 1983;Brown and Ariel 2009;Chu et al 2011a, b;Cohen and Yarom 1998;De Jaeger and Proteau 2003;de Solages et al 2008;Dizon and Khodakhah 2011;Eccles et al 1972b;Heck et al 2007;Holtzman et al 2006;Kolb et al 1997;Rokni et al 2007). While Purkinje cells do respond along parallel-fiber-activated beams in response to direct electrical stimulation of the molecular layer (Eccles et al 1966;Gao et al 2006;Wang et al 2011), when the cerebellum is activated from the sensory periphery, responding Purkinje cells are not found in beams, but instead are clustered in isolated patches (Bower and Woolston 1983;Dizon and Khodakhah 2011;Eccles et al 1972b;Gao et al 2006).…”
Section: What Do Parallel Fibers Do To Purkinje Cells?mentioning
confidence: 98%
See 1 more Smart Citation